GRPR Expression in Metastatic Cancers: A Review of Potential Application of GRPR-Radioligand Therapy - Callaud, Aurélien; Duan, Heying; Hindié, Elif; Morgat, Clément; Iagaru, Andrei (Seminars in nuclear medicine, 2025)
Gastrin-Releasing Peptide Receptor (GRPR) represents a promising molecular target for radionuclide therapy (TRT) across a variety of malignancies due to its overexpression in several tumor types, including prostate, breast, lung, melanoma, cervix, neuroblastoma, head and neck, and colon cancers. While expression patterns vary—with high GRPR expression notably observed in cervix and neuroblastoma cancers—tumor heterogeneity and metastatic profiles remain challenges for patient selection and therapy optimization. Recent advances in GRPR-targeted radiopharmaceutical development have focused on overcoming peptide instability and enhancing tumor uptake, exemplified by novel compounds such as AMTG with improved proteolytic resistance and albumin binding domains to extend circulatory half-life. Furthermore, innovative radionuclides like terbium-161, lead-212, copper-67, cobalt-58 m, and arsenic-77 offer enhanced therapeutic potential beyond the current standard of lutetium-177 through favorable decay characteristics including Auger electron emission and alpha-particle therapy. Preclinical and early clinical studies demonstrate encouraging tumor targeting and therapeutic efficacy with manageable toxicity profiles, particularly in prostate and cervix cancers. However, further investigation into GRPR expression heterogeneity, metastatic distribution, and safety is necessary to refine patient stratification and maximize clinical benefit. This evolving landscape positions GRPR-TRT as a versatile and potent approach, with the potential to expand targeted radionuclide therapy to a broader range of malignancies and improve outcomes in advanced cancers with limited treatment options.